Difference in HIV prevalence by testing venue: results from population level survey in Uganda. Issue 3 (4th March 2021) - Ouma, Joseph; Jeffery, Caroline; Valadez, Joseph J.; Wanyenze, Rhoda K.; Todd, Jim; Levin, Jonathan
ABSTRACT: Growing demand for use of Health Facility (HF) HIV testing data, in addition to other testing data to obtain district level HIV prevalence requires understanding the comparability of these various sources. We analysed the 2011 Uganda AIDS indicator survey data to assess: the proportion of people tested for HIV across Uganda by venue of testing; HIV prevalence ratio for those tested in a HF compared to those tested in community setting; [Katz, D., Baptista, J., Azen, S. P., & Pike, M. C. (1978 ). Obtaining confidence intervals for the risk ratio in cohort studies. International Biometric Society, 34 (3 ), 469 –474 . https://doi.org/10 .2307 /2530610] and factors associated with HIV positivity in each subgroup. Of the 11, 685 individuals, 8978 (77.1%) had ever tested for HIV in a HF. Fifty nine per cent tested in a HF in the 12 months preceding the survey (female: 5507, 72.7% versus male: 1413, 34.9%). HIV prevalence ratio was 1.8 times among those tested in a HF compared to those tested at community setting (10.9% [95% CI: 10.0–11.7] versus 6.2% [95% CI: 5.4–7.0]). Among HF testers, older age group, previously married and having no sexual partner was associated with significantly higher HIV prevalence. Using facility testing data for planning and decisions should take into consideration the elevated and varying HIV prevalence among individuals accessing HIV testing services at HFs as well as differences in their social-demographic characteristics.